Faktor-Faktor Yang Mempengaruhi Minat Beli Produk Fashion Halal: Systematic Literature Review - Desifa Pauzia; Muhammad Shiddiq; Amira Najwa Kamila; Nissa Ariyanto; Muhammad Afaf sidiq; Bimbie Ramadhan; Danish Mutia Farida; Novanka Aulia Rahma (Universitas Islam Negeri Imam Bonjol Padang, 2026)
This study aims to identify the dominant factors influencing purchase intention of halal fashion products, analyze their relationship with economic dynamics, and provide implications for the development of a sustainable industry in Indonesia. The method used is a Systematic Literature Review (SLR) through Google Scholar, Scopus, and ResearchGate databases with a publication range of 2015–2026. The results of the study indicate that consumer purchase intention is influenced by a combination of religious, psychological, social, and marketing factors. Religiosity and halal awareness play a major role in consumers prioritizing sharia principles. However, consumers still consider rational economic aspects such as material quality, fashionable design trends, comfort, and price alignment. This dynamic is reinforced by digital marketing strategies (such as Muslim influencers and Islamic branding) and social environmental support. This study concludes that a paradigm shift has occurred where halal fashion is now transformed into part of a modern identity and lifestyle (halal lifestyle). To optimize Indonesia's market potential, adaptive design innovation, digital branding optimization, and government synergy are needed to facilitate halal certification to build a strong supply chain ecosystem from upstream to downstream.